Teacher Monitoring of Students with ASD and Their Families During Lockdown: A Comparison Between Spain and Mexico - Carmen del Pilar Gallardo-Montes; María Jesús Caurcel-Cara; Antonio Rodríguez Fuentes; Christian Cid-González (COVID, 2025)
Since the establishment of the State of Alarm resulting from the current COVID-19 pandemic, lockdown, and quarantine have been imposed in most countries, with serious health, social, economic, and educational consequences. The health emergency caused by COVID-19 led to the closure of schools, forcing students from all over the world to stop attending schools and compromising the quality of care offered to students with autism spectrum disorder (ASD). In order to examine how teachers supervised students with ASD virtually during the lockdown period, and to determine whether families considered the support provided by teachers to be adequate, a cross-cultural study design was adopted. An ad hoc questionnaire was administered to 415 families in Spain and Mexico in April 2020. We calculated frequencies and carried out descriptive analyses, parametric inferential analyses, and correlations. Families reported that educational monitoring and contact with the family member with ASD during home lockdown was scarce, despite the provision of activities appropriate to their needs. Significant differences were found as a function of country, age of participant, age of family member with ASD, type of ASD, type of schooling, and length of lockdown. This study highlights the need to train teachers in inclusive digital education and to establish effective protocols for communication and follow-up with the families of students with ASD.